(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Magnetic manganese ferrite powder is synthesized via chemical co-precipitation and hydrothermal techniques are using chemical compound in metallic chlorides of manganese and iron. As a precipitant agent nemely sodium hydroxide (NAOH) are used. The performed calcinations temperature at 700°C for 6 hours. The investigation of the structural compound are prepared sample was identified through X-ray diffractometer (XRD) and The FT-IR absorption spectra analyses were used for the detection and confirmation of the chemical bonds in spinel ferrites nanoparticles. The investigation of magnetic property of manganese ferrite nanoparticles reveals that the saturation magnetization is high, hysteresis in the region of measured field strength.